2020
DOI: 10.7717/peerj.9541
|View full text |Cite
|
Sign up to set email alerts
|

Anti-COVID-19 multi-epitope vaccine designs employing global viral genome sequences

Abstract: Background The coronavirus SARS-CoV-2 is a member of the Coronaviridae family that has caused a global public health emergency. Currently, there is no approved treatment or vaccine available against it. The current study aimed to cover the diversity of SARS-CoV-2 strains reported from all over the world and to design a broad-spectrum multi-epitope vaccine using an immunoinformatics approach. Methods For this purpose, all available complete genomes were retrieved from GISAID and NGDC followed by genome multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 78 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…The SARS-CoV-2 S protein is regarded as a leading target in vaccine development ( Poh et al, 2020 , Samrat et al, 2020 , Pillay, 2020 ). Previous studies reported the identification of putative T cell epitopes using in silico tools ( Crooke et al, 2020 , Abraham Peele et al, 2020 , Jakhar et al, 2020 , Zaheer et al, 2020 ) and evaluated T cell responses using COVID-19 patients’ immune cells stimulated with SARS-CoV-2 S protein or mixed peptides (rather than discrete, individual peptide motifs) ( Grifoni et al, 2020 , Braun et al, 2020 ). Thus, we set out to identify virus-specific T cell epitopes using overlapping peptide stimulation in memory T cells from COVID-19-recovered patients, followed by ELISpot assay.…”
Section: Resultsmentioning
confidence: 99%
“…The SARS-CoV-2 S protein is regarded as a leading target in vaccine development ( Poh et al, 2020 , Samrat et al, 2020 , Pillay, 2020 ). Previous studies reported the identification of putative T cell epitopes using in silico tools ( Crooke et al, 2020 , Abraham Peele et al, 2020 , Jakhar et al, 2020 , Zaheer et al, 2020 ) and evaluated T cell responses using COVID-19 patients’ immune cells stimulated with SARS-CoV-2 S protein or mixed peptides (rather than discrete, individual peptide motifs) ( Grifoni et al, 2020 , Braun et al, 2020 ). Thus, we set out to identify virus-specific T cell epitopes using overlapping peptide stimulation in memory T cells from COVID-19-recovered patients, followed by ELISpot assay.…”
Section: Resultsmentioning
confidence: 99%
“…Antigenicity, Allergenicity, Cell Localization, and Immune System Response. The antigenicity scores of the polyvalent are constructed by Vaxijen 2.0 (threshold value: 0.5), Antigenpro (threshold value: 0.3) [46], and Secret-AAR [40]. Our construct showed an antigenicity score above the threshold value and considered antigenic.…”
Section: Molecular Modeling Of Epitopesmentioning
confidence: 99%
“…Further, studies following a combinatorial approach (H.-Z. Zaheer et al, 2020) are also expected to miss some of the epitopes reported in this study. It may however be noted that like most previous studies, the current study refrained from predicting potential B-cell epitopes, due to the computational complexities involved in the process and may be considered a limitation of this exercise.…”
Section: Discussionmentioning
confidence: 90%